2001
DOI: 10.1021/jo0103625
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Synthesis of 2,3-Dihydro-2-ylidene-1,4-benzodioxins

Abstract: Palladium-catalyzed condensation of benzene-1,2-diol with various propargylic carbonates afforded regio- and stereoselectively 2,3-dihydro-2-ylidene-1,4-benzodioxins. The reaction is suggested to proceed by the formation of a (sigma-allenyl)palladium complex, followed by the intermolecular attack of the phenoxide ion on this complex to generate a new (sigma-allyl)palladium complex in equilibrium with the corresponding (eta(3)-allyl)palladium complex. Intramolecular attack of the phenoxide ion afforded the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…We found that the cyclization process was often quite regio-and stereoselective, the major regioisomer being formed by intramolecular attack of the intermediate phenoxide ion on the more electrophilic terminus of the η 3 -allylpalladium intermediate. [23] We also found that the stereochemistry of the double bond in the resulting heterocycle depended on the substitution pattern of the propargylic carbonate: primary and secondary carbonates afforded mainly the (Z) alkene, while tertiary carbonates gave predominantly the (E) isomer. We thought that it would be interesting to extend this methodology to substituted catechols, in order to obtain 2-alkylidene-2,3-dihydro-1,4-benzodioxines bearing various substituents on the phenyl ring.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…We found that the cyclization process was often quite regio-and stereoselective, the major regioisomer being formed by intramolecular attack of the intermediate phenoxide ion on the more electrophilic terminus of the η 3 -allylpalladium intermediate. [23] We also found that the stereochemistry of the double bond in the resulting heterocycle depended on the substitution pattern of the propargylic carbonate: primary and secondary carbonates afforded mainly the (Z) alkene, while tertiary carbonates gave predominantly the (E) isomer. We thought that it would be interesting to extend this methodology to substituted catechols, in order to obtain 2-alkylidene-2,3-dihydro-1,4-benzodioxines bearing various substituents on the phenyl ring.…”
Section: Resultsmentioning
confidence: 69%
“…For this purpose, we choose methyl 1-methylprop-2-ynyl carbonate (2) as the propargylic carbonate, and catechols bearing electron-withdrawing or -donating groups at positions 3 or 4, namely 3-methoxybenzene-1,2-diol, 2,3-dihydroxybenzaldehyde, and 3-nitrobenzene-1,2-diol (1bϪd), and 4-methoxybenzene-1,2-diol, 3,4-dihydroxybenzaldehyde, and 4-nitrobenzene-1,2-diol (5aϪc) as the substituted diphenols. The condensation was performed as described previously, [23] in THF in the presence of the catalyst obtained by mixing [Pd 2 (dba) 3 ] and dppb. The results of the cyclization are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] In these reactions, two consecutive nucleophilic attacks occur. A nucleophile attacks at the central carbon of the Z 3 -allenyl/propargyl intermediate generated by reaction of a propargylic carbonate with Pd(0) to yield a p-allylpalladium intermediate, which is successively attacked by a second nucleophile.…”
Section: Introductionmentioning
confidence: 99%